A reciprocity approach for calculating the far-field radiation patterns of a center-fed helical microstrip antenna mounted on a dielectric-coated circular cylinder. - Martin, R.A.
This paper presents an efficient approach based on reciprocity for calculating the far-field radiation pattern of a center-fed helical microstrip antenna mounted on a circular cylinder. The reciprocity theorem is used to find a completely analytical solution to the problem assuming that the helical microstrip is sufficiently thin with a sinusoidal current distribution. Two degenerate cases of the helical microstrip antenna, i.e., an axially and an azimuthally fed half-wave cylindrical-rectangular patch, are examined and compared to known results in order to provide validation for the general analytical solution. Further comparisons are made between the analytical results and the results obtained using a numerically rigorous method of moments (MoM) computer code
Keywords: MoM computer code; Analytical solution; Axially fed half-wave patch; Azimuthally fed half-wave patch; Center-fed helical microstrip antenna; Conformal antennas; Cylindrical-rectangular patch; Dielectric-coated circular cylinder; Far-field radiation pattern; Far-field radiation patterns; Helical microstrip; Integral equations; Method of moments; Reciprocity theorem